Gut bacteria contribute to fenvalerate resistance in the tomato leafminer, Tuta absoluta - Ehsan Baradaran; Azam Mikani; Saeid Moharramipour; Mohammad Mehrabadi (Scientific Reports)
Abstract The tomato leafminer is a destructive pest causing significant damage to crops. Overreliance on insecticides has led to developing resistance in this insect pest. Microorganisms may benefit insects, including nutrient acquisition, digestion, immunity, and resistance to pesticides. Understanding these diverse interactions is crucial for effective management of pests and their resistance to pesticides. Here, we have investigated Here, we have investigated the role of gut bacteria in the development of fenvalerate-resistant tomato leafminer. The gut bacteria of fenvalerate-resistant (FR) and fenvalerate-susceptible (FS) populations were compared using Real-time PCR with group-specific primers. It was shown that the gut bacteria community of the two populations differed. The population of Actinobacteria and Gammaproteobacteria communities in the gut of FR larvae were greater than those in FS ones. Also, some of the gut bacteria cultured on NA medium containing fenvalerate were able to grow and degrade fenvalerate. 16S rRNA sequencing showed that Enterobacter spp (Gammaproteobacteria) was common in both populations. However, Micrococcus spp (Actinobacteria) was detected specifically in the resistant population. Fenvalerate bioassays with gut bacteria-free (germ-free) line and the gnotobiotic lines that have only Enterobacter spp (FRE), Micrococcus spp (FRM), Enterobacter spp and Micrococcus spp (FRE+M), demonstrated that the resistant ratio diminished in the gut bacteria-free (germ-free) line, while in the FRE+M line, resistant ratio was reduced by 15 percent. Our findings showed that the gut bacteria especially Enterobacter spp and Micrococcus spp are involved in developing resistant tomato leafminers to fenvalerate. Further investigations are required to identify the specific mechanisms of resistance, which could provide valuable insights for effectively controlling this pest.